Saltwater inflows and circulation dominantly influence Baltic Sea eutrophication (2010–2021) - Parn, Ove; Macias, Diego; Polimene, Luca; Stips, Adolf (Frontiers in Earth Science, 2025)
The Baltic Sea’s chronic eutrophication is conventionally attributed to anthropogenic nutrient inputs, but physical processes—such as stratification, saltwater inflows, circulation, and ice cover—play a critical yet understudied role in modulating ecosystem responses. While nutrient load reductions remain a cornerstone of management, the extent to which physical factors influence eutrophication dynamics remains unclear. To address this, we applied a coupled physical–biogeochemical model (2010–2021) to assess the relative impacts of physical conditions versus nutrient reductions. We implemented extreme and partly hypothetical hydrographic scenarios—not as forecasts, but as conceptual experiments—to examine how changes in physical drivers affect ecosystem functioning. Ecosystem responses were evaluated using chlorophyll-a concentrations and the Trophic Transfer Index (TTI), with separate Good Environmental Status (GES) assessments calculated for each indicator. Results show that physical factors had disproportionately large effects, altering GES-compliant areas by up to +4% (chlorophyll-a) and +7% (TTI), while nutrient load reductions had minimal impact (≤1.5%). Blocking North Sea inflows caused the most dramatic changes, increasing chlorophyll-a by up to +45% and reducing TTI by −29%, underscoring eutrophication’s sensitivity to ventilation dynamics. Over short periods, physical factors could outweigh even extreme nutrient reductions (−50% loads), potentially amplifying or counteracting intended management outcomes. These findings underscore the crucial role of physical drivers in Baltic Sea eutrophication and emphasize the importance of incorporating them into assessments of ecosystem recovery and management effectiveness.